PERSEPSI KONSUMEN TERHADAP GREEN MARKETING STARBUCKS MALL BOEMI KEDATON LAMPUNG - Nina Lelawati; Nani Septiana; Rahmat Fajar Ramdani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Abstract Environmental responsibility is a consumer perception of environmentally friendly management, particularly for a business. Environmental issues are becoming a new problem in the era of marketing.Green marketing can be a bad way to get people to buy from you."Green marketing" refers to satisfying customer needs, wants, and desires in relation to environmental preservation and upkeep. At Boemi Kedaton Mall in Lampung, the aim of this study is to ascertain how customers perceive Starbucks' green marketing.When it comes to the information about the subject that is the subject of the study, the type of research that is carried out is qualitative. In particular, the type of information that is examined can be a presumption, perspective, meeting, or quality of the individual or group that is the subject of the study.In order to process numerical data using statistical methods, qualitative methods are used to analyze the data. It is hoped that more precise measurement results will be obtained regarding the responses provided by respondents.The findings demonstrated that customers are at ease in the facility.Customers have two choices at every Starbucks location:smoking region or not.This is for the convenience of Starbucks customers entering the interior.Additionally, the ease with which information and promotions could be found on the Starbucks website piqued the interest of this study's respondents in the most recent promotions.